Students' Collaborative Skills in Designing Educandy-Based Interactive Learning Media - Wirandita, Amelia Prischa; Rohmah, Inayatur; Virgantoro, Eric Dwi; Putri, Safika Aisyah; Hardiansyah, Framz (Journal of Practice Learning and Educational Development, 2026)
In the growing digital era, the ability to collaborate is one of the essential skills that students must have. This article discusses how students can develop their collaboration skills through designing interactive learning media using the Educandy platform. This research was conducted through a qualitative method. The researcher used the systematic literature review (SLR) method in which the data made to write this article was sourced from articles and journals available on Google Scholar. The researcher started by looking for articles that are relevant to the title of this article, namely collaboration skills, designing, and interactive learning media. This article seeks to identify the development of students' collaboration skills in designing interactive learning media through the educandy platform